1993
DOI: 10.1115/1.2920965
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Analysis for Piston Skirts in Mixed Lubrication: Part II—Deformation Considerations

Abstract: This paper presents a mathematical model for piston skirts in mixed lubrication. It takes into account the effects of surface waviness, roughness, piston skirt surface profile, bulk elastic deformation and thermal distortion of both piston skirts and cylinder bore on piston motion, lubrication and friction. The corresponding computer program developed can be used to calculate the entire piston trajectory and the hydrodynamic and contact friction forces as functions of crank angle under engine running condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 0 publications
1
63
0
2
Order By: Relevance
“…Since the 1970s, several typical modellings considering surface roughness effect for mixed lubrication problems have been developed, such as the longitudinal-roughness flow model by Christensen [8], the average Reynolds equation by Patir and Cheng [9], and the asperity contact model by Greenwood and Tripp [10]. Zhu et al [11] studied the mixed lubrication problem of a piston-cylinder contact, focusing on the convex piston. Wang et al [12] analysed the journal-bearing conformal contacts under steady-state conditions, considering the combined effects of bearing deformation, surface roughness and asperity interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s, several typical modellings considering surface roughness effect for mixed lubrication problems have been developed, such as the longitudinal-roughness flow model by Christensen [8], the average Reynolds equation by Patir and Cheng [9], and the asperity contact model by Greenwood and Tripp [10]. Zhu et al [11] studied the mixed lubrication problem of a piston-cylinder contact, focusing on the convex piston. Wang et al [12] analysed the journal-bearing conformal contacts under steady-state conditions, considering the combined effects of bearing deformation, surface roughness and asperity interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [42,43] presented a two-part analysis. In the first part, they developed transient hydrodynamics of rigid bodies in contact.…”
Section: Introductionmentioning
confidence: 99%
“…The second part extended the approach to include gross piston distortions. They overcame the computation burden of the repeated time-dependent calculations for piston skirt deflection through use of an influence coefficient matrix, derived from their own FEA model [43]. Common to both their contributions was the use of low relaxation Newton-Raphson iterative solution for system dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Those authors have shown through an analytical model that piston skirt friction can be significantly reduced if the piston center of rotation is located in a favorable position. Zhu et al [88] numerically investigated piston motion, lubrication, and friction in mixed lubrication regime taking into account effects of surface waviness, roughness, surface profile, bulk elastic deformation, and thermal distortion of both piston skirt and cylinder bore. The proposed model was applied to a four-stroke automotive engine showing that good hydrodynamic lubrication can minimize the possibility of piston impact against the cylinder bore and reduce the frictional loss.…”
Section: Oil Lubricated Pistonmentioning
confidence: 99%